(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2011)
Laminar, natural convection heat transfer of air filling horizontal space between isothermal (cold) square enclosure and four isothermal (hot) cylindrical rods has been theoretically studied. Finite element method has been used to solve the conservation of governing equations by using software package (FlexPDE).Parametric study has been conducted for the range of Rayliegh number 103Ra105,Aspect ratio 0.11AR0.28. Results are presented in the form of streamlines, isotherms contours and Nusselt numbers. Results showed that the overall heat transfer increases with increasing of both Ra and AR. The values of mean Nusselt numbers are compared with data reported in Ref.[6] and[15], and good agreement has been achieved.